(untitled) (Journal of Engineering, 2019)
In this work, a simple and new method is proposed to simultaneously improve the physical layer security and the transmission performance of the optical orthogonal frequency division multiplexing system, by combining orthogonal frequency division multiplexing technique with chaotic theory principles. In the system, a 2-D chaotic map is employed. The introduced system replaces complex operations such as matrix multiplication with simple operations such as multiplexing and inverting. The system performance in terms of bit error rate (BER) and peak to average ratio (PAPR) is enhanced. The system is simulated using Optisystem15 with a MATLAB2016 and for different constellations. The simulation results showed that the BER of an unauthorized receiver reaches 0.5. Furthermore, the peak-to-average-power-ratio (PAPR) of the transmitted OFDM signal can be decreased by about 0.8 dB at BER equal to 10^-4.